2009
DOI: 10.1097/mou.0b013e32832f0d5a
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy of a renal mass: where are we now?

Abstract: There is a trend in increasing interest and accuracy on the subject of percutaneous biopsy of renal masses as well as a decreasing trend in the rate of nondiagnostic biopsies. In the small renal masses, most likely to be benign, a diagnostic percutaneous biopsy may have a definitive role. However, the higher rate of nondiagnostic results in this population calls for prospective studies with standard definitions and when possible homogenous index test to properly assess the diagnostic performance of the biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…In fact most authors [24,25,27] describe a greater sensitivity of CB, except Heilbrun et al, who reported a greater sensitivity of FNAB [26]. However, these authors use a 20G needle for CB, unlike most of the others, who used 18G needles; furthermore Heilbrun's case series is not among the largest ones.…”
Section: Discussionmentioning
confidence: 68%
“…In fact most authors [24,25,27] describe a greater sensitivity of CB, except Heilbrun et al, who reported a greater sensitivity of FNAB [26]. However, these authors use a 20G needle for CB, unlike most of the others, who used 18G needles; furthermore Heilbrun's case series is not among the largest ones.…”
Section: Discussionmentioning
confidence: 68%
“…34 Laguna and colleagues identified cancer in 71% of repeat biopsies, and 78% of all cases with a non-diagnostic initial biopsy. 45 Thus, an indeterminate initial biopsy should not be taken as reassurance regarding the malignant potential of the mass.…”
Section: N1mentioning
confidence: 99%
“…A recent review by Laguna and colleagues noted that 46.4% of non-diagnostic biopsies were followed by repeat biopsy or surgery; cancer was present in 78.5% of all specimens, including 71% of repeat biopsies. 6 Changes to the American Joint Committee on Cancer (AJCC) staging of renal cell carcinoma (RCC) were recently released in the 7th edition of the AJCC Cancer Staging Manual.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%